FABRIKASI DAN KARAKTERISASI PITA SUPERKONDUKTOR BI-2212/AG MONOFILAME - Maulana, Alan
Composite Bi-2212/Ag superconductor tapes had been fabricated using Powder in Tube method. The superconductor powder with substitution of Bi by Pb atoms from 0% to 30% molar ratio had been obtained without loosing the properties of superconductivity. The highest volume fraction of Bi-2212 phase was obtained by powder with 10% molar ratio of Pb. This sample also results in the highest critical temperatur with Tc onset = 72,63 K. The x-ray difracton paterns of the superconductor tapes processed by partial melting at 5, 10 and 15 minutes at 870 Â°C without further annealing or further annealed for 100 hours at 825 Â°C produced XRD paterns characterized by the sole appearance of (001) diffraction peaks with 1 equal to even numbers. The FWHM (Full Width at Half Maximum) of the peaks were also reduced by the annealing process indicating further growth of the crystal grain and improvement of grain alignment as well as the reduction of residual stress